2014
DOI: 10.1002/ar.22939
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Observation of Mucosa‐Associated Lymphoid Tissue in the Large Intestine of Bactrian Camels (Camelus bactrianus)

Abstract: The structure and distribution of the mucosa-associated lymphoid tissue (MALT) throughout the large intestine of 10 Bactrian camels were comparatively studied by anatomical and histological methods. The results showed that Peyer's patches (PPs) were mainly located on the mucosal surfaces of the entire ileocecal orifice, the beginning of the cecum and the first third of the colon. The shape of PPs gradually changed from "scrotiform" to "faviform" along the large intestine with the scrotiform PP as the major typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…Histomorphological examination and photographic documentation were made for jejunal villus height and crypt depth (at 10× magnification objective lens and eyepiece), jejunal epithelial height, intra-epithelial lymphocytes and stromal lymphocytes infiltration (40× objective lens and 10× eyepiece) and brush border integrity (100× objective lens and 10× eyepiece). The density of GALT structures was evaluated by counting the number of lymphoid follicles visible in 10 fields of view at 4× magnification [22]. The intra-epithelial lymphocyte infiltration was evaluated based on the following scoring scale: normal, slight, moderate, and severe, corresponding to 0-1, 10-15, 15-20 and >20 lymphocytes/100 enterocytes, respectively.…”
Section: Intestinal Morphometry and Histopathologymentioning
confidence: 99%
“…Histomorphological examination and photographic documentation were made for jejunal villus height and crypt depth (at 10× magnification objective lens and eyepiece), jejunal epithelial height, intra-epithelial lymphocytes and stromal lymphocytes infiltration (40× objective lens and 10× eyepiece) and brush border integrity (100× objective lens and 10× eyepiece). The density of GALT structures was evaluated by counting the number of lymphoid follicles visible in 10 fields of view at 4× magnification [22]. The intra-epithelial lymphocyte infiltration was evaluated based on the following scoring scale: normal, slight, moderate, and severe, corresponding to 0-1, 10-15, 15-20 and >20 lymphocytes/100 enterocytes, respectively.…”
Section: Intestinal Morphometry and Histopathologymentioning
confidence: 99%
“…However, the studies about the different mucosal immune inductive sites of gastrointestinal tract has only received few attentions. Hence, based on our previous histological and structural studies of ALNA and ileal PPs in Bactrian camels [ 16 , 18 , 21 23 ], 16S rDNA-Illumina Miseq sequencing was used to comparatively analyze the bacteria community characteristics in ALNA and ileal PPs of Bactrian camels, moreover, the biological information hidden in them were revealed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Study has shown that the intestinal barrier plays an important role in SAP ( Tian et al, 2013 ). The mucosa-associated lymphoid tissues in intestine constitute the intestinal immune barrier to effectively prevent the invasion of bacteria and endotoxin (ET, lipopolysaccharide) from intestine into the blood ( ZhaXi et al, 2014 ). However, bacteria and ET may pass through the intestine into the sterile abdominal cavity (peritoneum) to cause serious complications when the intestinal barrier function is weakened or damaged ( Vaishnavi, 2013 ).…”
Section: Introductionmentioning
confidence: 99%